2021
DOI: 10.3390/ijms222312928
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Stiffness Modulates the Non-Linear Response to Stretch of the Extracellular Matrix in Pulmonary Fibrosis

Abstract: Pulmonary fibrosis (PF) is a progressive disease that disrupts the mechanical homeostasis of the lung extracellular matrix (ECM). These effects are particularly relevant in the lung context, given the dynamic nature of cyclic stretch that the ECM is continuously subjected to during breathing. This work uses an in vivo model of pulmonary fibrosis to characterize the macro- and micromechanical properties of lung ECM subjected to stretch. To that aim, we have compared the micromechanical properties of fibrotic EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Therefore, biomechanical characterizations of the decellularized tissue were obtained, which indicated similar stiffness for dLu and dLN, with a notable variability in macro-scale stiffness for dLN. Although the obtained mechanical properties (Young’s Modulus) of dLu are comparable to literature, these properties are only known for animal-derived decellularized ECM, non-decellularized human ECM or engineered hydrogels ( 58 62 ), extending the relevance of this study. Mechanical characterization of human lymph node ECM is absent in literature.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, biomechanical characterizations of the decellularized tissue were obtained, which indicated similar stiffness for dLu and dLN, with a notable variability in macro-scale stiffness for dLN. Although the obtained mechanical properties (Young’s Modulus) of dLu are comparable to literature, these properties are only known for animal-derived decellularized ECM, non-decellularized human ECM or engineered hydrogels ( 58 62 ), extending the relevance of this study. Mechanical characterization of human lymph node ECM is absent in literature.…”
Section: Discussionsupporting
confidence: 60%
“…Our results show an increase in elastin in the bleomycin-treated lungs with time, peaking at day 28, whilst in the PBS-treated lungs its content peaks at day 14 and is followed by a decrease. Thus, we can hypothesise that the presence of elastin might contribute to the turnover of the disease, as previous results reported by our lab suggested that there is a transition of behaviour from strain-hardening to strain-softening of the ECM that might work as a protection mechanism of the lung to prevent fibroblasts of proliferating after their initial activation [ 42 ]. The increase in elastin in the PBS-treated samples could be partly responsible for this turnover due to its physical role on the mechanical response of the lung ECM.…”
Section: Discussionmentioning
confidence: 75%
“…CD11b has been reported as a key biomarker in immune cells for the progression of diseases like cancer and autoimmunity 25,[28][29][30][91][92][93] . Given the growing evidence that cell elasticity and fluidity suffer alterations in disease, adhesion and mechanics of immune cells may appear as relevant biomarkers 26,[94][95][96][97][98][99][100][101][102][103] .…”
Section: Discussionmentioning
confidence: 99%